Uji Kemampuan Partikel KMnO4 Teremban Dalam Karbon Aktif Tempurung Kelapa Sawit Terhadap H2S Dalam Reaktor Biogas Unggun Tetap (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2023)
Biogas consists mainly of methane from activities of an-aerobic microorganisms. Biogas made from organic matter such as biomass (vegetable and fruit waste) such as those in the Gamping market in Yogyakarta-Indonesia. One of the problems in biogas is the content of H2S gas which in certain quantities is toxic, causing corrosion of the biogas apparatus, reducing combustion efficiency and causing acid rain. The aim of the study was to remove H2S gas in a fixed bed biogas reactor using 20% KMnO4 impregnation on activated carbon of palm kernel shells was pre-oxidation treatment using H2O2 (20% 2KMnO4-KATKS-H2O2). Biogas flowed into fixed bed reactor was containing 20% 2KMnO4-KATKS-H2O2 particles to oxidize H2S gas. The first variation is H2S in a nitrogen mixture flow on to fixed bed reactor at 3 temperatures, namely 30, 40 and 50°C. The second variation is the mass of KMnO4 in the fixed bed biogas reactor varied by 4 grams, 4.5 grams and 5 grams. Research results of H2S gas in a fixed bed reactor with uncontrolled; 30°C; 40°C; 50°C the concentration decreased successively 98.48%; 98.7%; 98.45% and 98.36%. H2S gas with a concentration of 20 ppm in a fixed bed biogas reactor decreased with variations of 4 grams, 4.5 grams and 5 grams respectively, namely 70%; 85%; 90%. This research has a novelty used the KMnO4 carrier material in the form of activated carbon kernel shells, using a continuous fixed bed reactor and the incoming material is in the form of biogas. Keywords: Biogas, Fruit waste, H2S, KMnO4, KATKS, H2O2, Fixed bed